At the Outset of Georgian Criminology Briefly about Giorgi Mikheil Shengelaia (November 1897 - March 1950) - Tsulaia, David (Journal of Law, 2019)
Nowadays, in Georgia, the criminologists and lawyers are almost unaware about the personality of Giorgi Shengelaia. This should not be surprising, since there is nothing mentioned about him and his professional achievements in Georgian legal and criminological literature. Whereas, G. Shengelaia had been lecturing for years at the Law faculty of Tbilisi State University, as well as delivering lectures for lawyers, police officers, prosecutors and judges. Besides the pedagogical activities, G. Shengelaia was also keenly involved in scientific research activities. He had also been researching issues related to criminology and criminal law. Due to this fact, we decided to briefly present Mr. Shengelaia’s personality and his works before the the Georgian public. In the course of research, we have obtained just few information regarding his biography and professional activities that we would like to review and discuss about Mr. G. Shengelaia. We hope that in the near future we will find more and more interesting materials that we be definitely introduced before public.